Redistributive Consequences of Abolishing Uniform Contribution Policies in Pension Funds - Damiaan Chen; Sweder van Wijnbergen (Tinbergen Institute, 2017)
Abstract In a pension system with uniform policies for contribution and accrual, each participant has the same contribution rate and accrual rate independent of the age at the time of payment. This is not actuarially fair because the investment horizon of young participants is longer than the investment horizon of the elderly. This paper shows the presumably unintended redistributive effects of a uniform contribution system and the consequences of switching from uniform policies to an actuarially fair system. We first analyze a stylized model with three overlapping generations to show the intuition behind these effects. Then, we quantify these effects in a more detailed model with multiple overlapping generations, realistic parameters and more detailed information on the income distribution, calibrated on the Dutch funded pension system. We first use this model to show that there is a substantial transfer of income from poor to wealthy participants under a pension scheme with uniform policies: about 10 billion euros are transferred from poor to wealthy participants under the current uniform contribution policies in the Netherlands. We then calculate the gross aggregate transition effect of abolishing the uniform policy pension for an actuarially fair system to be about 37 billion euros (or about 5% of the Dutch GDP). For each cohort, the redistributive effects are less than 5% of their total pension.
Keywords: G23; J32; 330; uniform policies; pension funds; transition; income inequality